The present educational process as a state of the future social system - I. V. Petrova (Дискурс)
Introduction. The work considers formation possibilities of the present educational process for Russian students to provide the future digital economy with staff.Materials and methods. The frame analysis “institutional socialization of students” is the author’s cognitive strategy that functionally integrates interconnected slots of the social process: the state, an educational institution, a student, and serves as a basis for a sociological study of the problem.Results. Developments and recommendations are based on data analysis of a comprehensive empirical study of macro-, meso- and micro-levels of students social and professional development system in higher education. The construction of educational, social and scientific activities of students is proposed to be based on the idea of academic student groups structural and functional mobility by means of the author's social technology “Group Development Wheel”. Development of students personalities is associated with the development of a self-governing educational group in the project format of professional training at a higher education institution.Discussion. The advisability of strengthening the social design direction of future specialists by using the resources of art and sociology through the mechanism of educational process diffusion is also explained.Conclusion. The development of a human capital in education is the key to a society successful position at the digital level, both for the education system and for an individual.